Information literacy skills of librarians at the UIN Maulana Malik Ibrahim Malang Library as a literacy agent based on the Big Six Model - Anjani, Marinda; Qolbina, Dhia Shifa (Maliki Interdisciplinary Journal, 2024)
Libraries are institutions that provide information sources managed by librarians. In tertiary institutions, the library level is higher and the users are mostly academics such as lecturers, researchers or students. So that librarians in higher education libraries must have knowledge and information literacy skills well in order to serve users in fulfilling their information needs. This research was conducted on librarians at the Central Library of UIN Malang. The purpose of this research is to find out how information literacy skills of librarians act as literacy agents in the UIN Malang Library. The method used in this research is descriptive qualitative method. Data collection was carried out by observation, interviews, and literature study on the topics studied. This research was conducted on librarians representing each field in the UIN Malang Library. Determination of respondents using purposive sampling technique with the criteria of someone who has the ability and knowledge about library management well. There were five respondents from four areas of library services covering collection development and processing, library services, education and training programs, and IT development. This information literacy analysis for librarians uses The Big Six model as a reference for research implementation. The results of this study stated that the information literacy level of librarians at the UIN Malang Library was quite good. The six stages of The Big Six model can be carried out by respondents. So that they can be grouped into librarians who have good information literacy skills and mastery of technology as agents of information literacy.